Method of Strengthening Arm Muscles Against the Ability of the Tennis Flat Service Stroke (Experimental Study in Students of Muhammadiyah University of Surakarta) - Marvian Dwi Harjanto; Gatot Jariono (CV. Inara, 2021)
The purpose of this study is to Method of Strengthening Arm Muscles Against the Ability of the Tennis Flat Service Stroke (Experimental Study in Students of the Muhammadiyah University of Surakarta). Arm muscle strength is a component of the physical condition needed in the implementation of some court tennis techniques such as the implementation of flat service techniques. In the sport of court tennis, the ability of service is indispensable, and the quality of a player's service is affected by the quality of the arm muscles. To be able to perform a good and precise punch requires an element of strength from a group of muscles that support the movement. Of the many, the most dominant muscles are the arm muscles. This study aims to Find Out the Effect of Arm Muscle Strengthening Exercise Methods on The Ability of Flat Tennis Court Service Punches in UMS Tennis UKM players. experimental methods. The design of this study uses One Group Pretest and Posttest Design with arm muscle strength instrument test using pushup techniques and service skills using the Hewitt Tennis Achievement Test. The population using UMS Tennis Court UKM students amounted to 50 people. the sample consisted of 13 Students of UMS Tennis Court UKM. Purposive sampling techniques have certain conditions. Variable pushups increased in number from pretest 182 and posttest 213 with an average of 14 to 16.4 meaning an increase in the number of values by 31 and an average of 2.4, Variable service increased in number from 123 to 207 and an average of 9.47 to 15.9. This means that there is an increase in the number of values of 84 and an average of 6.43, this is supported by the results of the hypothesis that shows that the value of sig. 2-tailed) of pretest and posttest pushup is 0.000 while sig value. 2-tailed) of pretest and posttest service is 0.000. Sig value. (2-tailed) push-ups < 0.05 meaning there is a significant difference between pretest and posttest, while sig values. (2-tailed) service < 0.05 means that there is a significant difference between pretest and posttest. So it can be concluded that there is an influence of arm muscle strengthening exercise methods on the ability of flat tennis court service punches in players of the Muhammadiyah University of Surakarta, so the hypothesis of this study is accepted.